Research on Evolution of Population and Economy Spatial Distribution Pattern in Ecologically Fragile Areas: A Case Study of Ningxia, China - Li, Jiaxin; Huang, Wei (Frontiers in Environmental Science, 2022)
Sustainable development is particularly important for ecologically fragile areas. The relationship between population and economy is a key factor affecting the sustainable development of ecologically fragile areas. This study uses the population and regional GDP data of 22 districts (cities, counties, etc.) under the jurisdiction of Ningxia from 2010 to 2019 to analyze regional gravity center, geographic concentration, inconsistency index, and spatial autocorrelation, therefore uncovers the population and economy spatial distribution pattern evolution of Ningxia. The results show that: 1) The population and economy in Ningxia is in an unbalanced spatial distribution pattern of “high in North and low in Middle and South,” and their geographical connection is relatively close. 2) The imbalance of economic development in Ningxia exceeds that of population development, but their relationship is becoming increasingly coordinated. 3) Ningxia’s economically advanced zones and coordinately developing zones are mainly concentrated in the north, and most of the central and southern areas have always been economically lagging. 4) There is a strong trend of agglomeration in Ningxia’s population and economic distribution. The districts with similar inconsistencies between population and economy tend to be spatially agglomerated, and the overall LL-type and HH-type agglomeration trend is significant. This research provides an important basis for the formulation of population and economic policies in ecologically fragile areas.